PAPER Perancangan Sistem Informasi Ticket Bookin Online Travel Umrah Studi Kasus PT.Sukkari Halal Tour: PAPER Perancangan Sistem Informasi Ticket Bookin Online Travel Umrah Studi Kasus PT.Sukkari Halal Tour - raja, abrar; Elsi Titasari Br Bangun (Computer Science and Information Technology, 2025)
This study focus to design an online umrah ticket booking information system of PT.Sukkari Halal Tour to enhance service efficiency and information transparency. The Prototype method was employed, covering stages such as requirement gathering, prototype development, evaluation, coding, testing, and implementation. The result include the design of a use case diagram, activity diagram, sequence diagram, and class diagram, which comprehensively illustrate the system flow. The system accomondates two actor: pilgrims and administrator with features like online registration, document verification, digital payment, and travel packages management. The research concludes that this system simplifies administrative processes and improves user experience.